2008
DOI: 10.1007/s00441-008-0574-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myoblast differentiation by Sfrp1 and Sfrp2

Abstract: Secreted Frizzled-related proteins (Sfrps) are extracellular regulators of Wnt signalling and play important roles in developmental and oncogenic processes. They are known to be upregulated in regenerating muscle and in myoblast cultures but their function is unknown. Here, we show that the addition of recombinant Sfrp1 or Sfrp2 to C2C12 cell line cultures or to primary cultures of satellite cells results in the inhibition of myotube formation with no significant effect on the cell cycle or apoptosis. Even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Although we found that PDZRN3 inhibits Wnt–β-catenin signaling during osteoblast differentiation, it might not inhibit such signaling during myogenic differentiation, given that our previous study showed that depletion of PDZRN3 inhibited myogenic differentiation without affecting the expression of myogenin (Ko et al , 2006). Wnt–β-catenin signaling is thought to promote the differentiation of myoblasts into myotubes in part by increasing the expression of myogenin (Rochat et al , 2004; Descamps et al , 2008). PDZRN3 might thus contribute to different signaling pathways during osteoblast and myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that PDZRN3 inhibits Wnt–β-catenin signaling during osteoblast differentiation, it might not inhibit such signaling during myogenic differentiation, given that our previous study showed that depletion of PDZRN3 inhibited myogenic differentiation without affecting the expression of myogenin (Ko et al , 2006). Wnt–β-catenin signaling is thought to promote the differentiation of myoblasts into myotubes in part by increasing the expression of myogenin (Rochat et al , 2004; Descamps et al , 2008). PDZRN3 might thus contribute to different signaling pathways during osteoblast and myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…After 50 μM PQ was treated for 48 h, cell viability was measured using a troponin T (a muscle differentiation marker, clone JLT-12; Sigma), as described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, exposure of adipose cells to increasing 4-HNE concentrations causes biological events associated with the development of IR. In this context, 4-HNE may cause a selective impairment of insulin signaling in adipocytes by the downregulation of IRS-1 and upregulation of p38 MAPK activity, thereby leading to increased production of lactate and impaired adiponectin secretion [132][133][134]. Nonetheless, in differentiating (pre)adipocytes, oxidative stress can induce intracellular 4-HNE production, which in turn activates p38 MAPK [135].…”
Section: -Hydroxynonenalmentioning
confidence: 99%